We are using substitution to solve this problem.
y=3x+1
y=-2x+3
Make these equal each other: 3x+1=-2x+3
Add 2x to both sides: 3x+2x+1=-2x+2x+3
= 5x+1=3
Subtract 1 from both sides; 5x+1-1=3-1
= 5x=2
Divide 5 from both sides: 5x/5=2/5
X= 2/5
Plug X into one of the equations: y=3(2/5) +1
y=11/5(2.2)
(2/5,11/5)
Answer: True i believe
Step-by-step explanation:
No no. no no n on o n in o n o b o n
Answer:
A) 7x^2-7x+15
Step-by-step explanation:
f(x) = 4x2 - 5x + 7,
g(x) = 3x2 - 2x + 8
f(x) +g(x) =
4x^2 - 5x + 7 + 3x^2 - 2x + 8=
7x^2-7x+15